Mutagenic and genotoxic effect of hydroxyurea - Santos, Jean L. [UNESP]; Bosquesi, Priscila L. [UNESP]; Almeida, Adelia Emilia de [UNESP]; Chin, Chung Man [UNESP]; Varanda, Eliana Aparecida [UNESP] (My University, 2011)
The hydroxyurea, a cytotoxic drug, is the mainly available therapeutical strategy for the treatment of sickle cell disease. This study aimed to evaluate the mutagenic and genotoxic potential of the hydroxyurea through the Salmonella/Microsome assay and micronucleus test in peripheral blood of mice. The doses were evaluated at 29.25-468 μmol/plate in Salmonella/Microsome assay in presence and absence of metabolic activation the drug. In the micronucleus test the doses were evaluated at 12.5; 25; 50; 75 and 100 mg/kg. The results show that hydroxyurea present mutagenic activity in TA98 and TA100 in doses above 117 μmol/plate and 234 μmol/plate respectively. The drug induced a significant increase in the frequency of micronuclei in reticulocytes of mice at concentrations of 50, 75 and 100 mg/kg, compared to negative control (water). These results demonstrated the mutagenic and genotoxic potential of hydroxyurea. © 2011 Santos et al.
Keywords: Genotoxicity; Hydroxyurea; Micronucleus test; Mutagenicity; cyclophosphamide; hydroxyurea; water; animal cell; animal experiment; animal model; bacterial strain; blood analysis; controlled study; drug blood level; drug dose comparison; female; genotoxicity; male; metabolic activation; micronucleus test; microsome; mouse; mutagenicity; nonhuman; reticulocyte count; Salmonella typhimurium; concentration response; drug effect; mutagenic activity; toxicity testing; Mus